2016
DOI: 10.20517/2394-4722.2015.82
|View full text |Cite
|
Sign up to set email alerts
|

Nibrin expression in oral squamous cell carcinoma: association with clinicopathological parameters

Abstract: Aim:The present study sought to discover the role of Nibrin protein in 100 patients with oral squamous cell carcinoma (OSCC) and its potential relationship with clinicopathological parameters. Methods: Nibrin expression was evaluated immunohistochemically using the modified H-score method. Results: The present study included 20% of patients with stage I disease, 22% of patients with stage II disease, 18% of patients with stage III disease, and 40% of patients with stage IV disease. Nibrin showed a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The scoring system has already been published in our previous literature . All sections were scored independently by two independent researchers in a blinded fashion.…”
Section: Methodsmentioning
confidence: 99%
“…The scoring system has already been published in our previous literature . All sections were scored independently by two independent researchers in a blinded fashion.…”
Section: Methodsmentioning
confidence: 99%
“…Nibrin protein plays an important central role in double-stranded breakage repair pathway; oncoproteins are responsible for the activation of mutated nibrin which further induces the epithelial mesenchymal transition increasing the invasiveness and metastasis in the later stages of head and neck cancer [29]. Another study by Jigna H Dave et al in 2016 also showed similar findings as significant inverse-correlation of Nibrin over expression was associated with tumor size and tumor stage [14].…”
Section: Discussionmentioning
confidence: 80%
“…Some recent studies have reported abbarent NBS1expression in proliferating oral tissues suggesting a potential to predict carcinogenic process early on [14,15]. However, the status of NBS1 in subset of oral cancer from our population remains unknown.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations